Extremozymes: Challenges and Opportunities on the Road to Novel Enzymes Production - Blamey-Alegria, J (Elsevier Ltd, 2024)
Extremozymes, enzymes derived from extremophilic organisms, have gained significant attention in industrial applications due to their remarkable resistance to extreme conditions. Their unique properties offer advantages over traditional mesophilic enzymes, making them valuable for applications in biocatalysis, bioremediation, and biotransformations. However, the discovery and downstream processing of them still presents challenges. Native microorganisms that produce extremozymes often exhibit slow growth, resulting in low quantities of specific enzymes. On the other hand, the heterologous expression of extremozymes can be complex, involving challenges such as rare codon usage, formation of secondary mRNA structures, misfolding, aggregation, and inactivation of the enzymes in several cases when they are expressed in conventional mesophilic hosts. In this review, we address the challenges associated to the discovery and production of novel extremozymes. Furthermore, we explore current approaches to overcome these challenges, including use of alternative expression systems through next generation industrial biotechnology (NGIB), cell-free protein synthesis (CFPS), culturomics, new metagenomic approaches, artificial intelligence (AI), among others. © 2024 Elsevier Ltd